PENDAMPINGAN LAPORAN KINERJA KEPALA SMK BUSTANUL FALAH UNTUK PENGUATAN KEPEMIMPINAN PENDIDIKAN BERKELANJUTAN - Imam Wahyono; Kholilur Rahman; Ahmad Aziz Fanani; Fathi Hidayah; M. Hafil Birbik; Riza Faishol (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
The transition of school leadership requires a performance report that documents achievements, challenges, and best practices during the principal’s tenure as a form of accountability and as a foundation for future school development planning. This community service activity aimed to assist the preparation of the performance report of the principal of SMK Bustanul Falah for the 2022–2026 term, identify the school’s achievements and challenges, and formulate strategic recommendations for improving educational quality. The method employed was participatory mentoring with a reflective-evaluative approach, consisting of several stages: needs analysis, data collection and verification, report drafting assistance, joint review and reflection, and the formulation of school development recommendations. The results indicate that the mentoring process helped the school to inventory, verify, and organize various supporting documents that were previously scattered across different units, thereby enabling the performance report to be compiled in a more systematic, comprehensive, and data-driven manner. In addition, the activity produced an identification of achievements, challenges, and best practices during the principal’s leadership, which served as the basis for strategic recommendations. These recommendations include strengthening educational leadership, improving teaching quality, developing human resources, enhancing partnerships, and refining school governance. Program sustainability was achieved through the formulation of a school development roadmap, which can serve as a reference for program planning and decision-making in subsequent leadership periods.